Aerosol particle shrinkage event phenomenology in a South European suburban area during 2009–2015. (July 2017) - Alonso-Blanco, E.; Gómez-Moreno, F.J.; Núñez, L.; Pujadas, M.; Cusack, M.; Artíñano, B.
Abstract: A high number of aerosol particle shrinkage cases (70) have been identified and analyzed from an extensive and representative database of aerosol size distributions obtained between 2009 and 2015 at an urban background site in Madrid (Spain). A descriptive classification based on the process from which the shrinkage began is proposed according which shrinkage events were divided into three groups: (1) NPF + shrinkage (NPF + S) events, (2) aerosol particle growth process + shrinkage (G + S) events, and (3) pure shrinkage (S) events. The largest number of shrinkages corresponded to the S-type followed by NPF + S, while the G + S events were the least frequent group recorded. Duration of shrinkages varied widely from 0.75 to 8.5 h and SR from −1.0 to −11.1 nm h −1 . These processes typically occurred in the afternoon, around 18:00 UTC, caused by two situations: i) a wind speed increase usually associated with a change in the wind direction (over 60% of the observations) and ii) the reduction of photochemical activity at the end of the day. All shrinkages were detected during the warm period, mainly between May and August, when local meteorological conditions (high solar irradiance and temperature and low relative humidity), atmospheric processes (high photochemical activity) and availability of aerosol-forming precursors were favorable for their development. As a consequence of these processes, the particles concentration corresponding to the Aitken mode decreased into the nucleation mode. The accumulation mode did not undergo significant changes during these processes. In some cases, a dilution of the particulate content in the ambient air was observed. This work, goes further than others works dealing with aerosol particles shrinkages, as it incorporates as a main novelty a classification methodology for studying these processes. Moreover, compared to other studies, it is supported by a high and representative number of observations. Thus, this study contributes to get a better understanding of this type of atmospheric aerosol transformations and its features. Highlights: Aerosol size distributions measured in a suburban area were analyzed for 6.5 years. The highest number of shrinkages reported to date has been recorded in this site. A classification methodology for studying these processes has been proposed. Shrinkage events took place during the warm period in the afternoon. Atmospheric dilution and a decrease in photochemical activity caused these processes.